Obtenção de biomassa de Babosa para produção de biodiesel - Almeida, Natalia Maria Diniz Pereira (Universidade Federal Rural do Semi-Árido, 2018)
Society has radically changed the emissions of polluting gases, originating from a series of human activities, and a great part of these gases come from the burning of the military, mainly in theautomobile industries. This context is biofuel emerges to alternative oil in the oil, between them is the biodiesel, that is one carbure biodegradable, renewable and solarly to the diesel. Biodiesel can be obtained from biomasses rich in triacylglycerides of vegetable oils, animal fats and residual oils. In this scenario, Brazil, through a territorial extension, has a variety of plant and vegetable species that try out the methods of extracting biomass from the Aloe Vera species, popularly known as slug, xrophyites plant adapted for survival in arid regions. The oils were extracted with commercial soybean oil in the proportions of 25%, 50% and 75% at room temperature conditions (Cold) and under heating at 60 ° C (Hot), and synthesized in biodiesel by basic transesterification in basic media. The biodiesel produced from hot-extracted biomass had yields higher than 50%, the yield of the biodiesel obtained from the biomass extracted in the cold, also had a good yield, being of the biodiesel BAF1 the highestpercentage of yield. The physicochemical analyzes carried out on biodieses presented results within the values required by the ANP. The analyzes included the acidity index ranging from 0 to 0.128, the saponification index, ranging from -7.0125 to 21, 0375, besides the values of pH and combustion test. All the results obtained by this study indicate the environmental and sustainable viability of obtaining biodiesel using Aloe Vera biomass.
Monografia
Keywords: Biomassa; Biomass; Babosa; Babosa; Biodiesel; Biodiesel; Sustentabilidade; Sustainability; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA